Design and Mechanistic Study of Highly Durable Carbon-Coated Cobalt Diphosphide Core–Shell Nanostructure Electrocatalysts for the Efficient and Stable Oxygen Evolution Reaction - Alsabban, Merfat M; Yang, Xiulin; Wahyudi, Wandi; Fu, Jui-Han; Hedhili, Mohamed. N; Ming, Jun; Yang, Chih-Wen; Nadeem, Muhammad A; Idriss, Hicham; Lai, Zhiping; Li, Lain-Jong; Tung, Vincent; et al. (ACS applied materials & interfaces, 2019)
The facile synthesis of hierarchically functional, catalytically active, and electrochemically stable nanostructures holds a tremendous promise for catalyzing the efficient and durable oxygen evolution reaction (OER) and yet remains a formidable challenge. Herein, we report the scalable production of core–shell nanostructures composed of carbon-coated cobalt diphosphide nanosheets, C@CoP2, via three simple steps: (i) electrochemical deposition of Co species, (ii) gas-phase phosphidation, and (iii) carbonization of CoP2 for catalytic durability enhancement. Electrochemical characterizations showed that C@CoP2 delivers an overpotential of 234 mV, retains its initial activity for over 80 h of continuous operation, and exhibits a fast OER rate of 63.8 mV dec–1 in base.